Syair Gulung: Perkembangan Dan Fungsinya Sebagai Pendidikan Moral - Fitrah Fadilla; Yosafat Kevin; Novita Sari; Haris Firmansyah (Jayapangus Press, 2021)
The purpose of this study is to describe how the development of rolled verse and how the implementation of moral education in the community of Ketapang regency. The method used in this research is qualitatively de-destructive. The result of the findings of this study is this rolled verse brought by da'i or preachers to the Land of Kayong as a medium to spread islam. And some of them (Malay people in Ketapang Regency) believe Ayat Gulung existed long before the entry of Islam in Ketapang this is because malay people are happy with literature and are inseparable from malay people's lives. Ketapang roll verse contains a lot of moral education values that are values related to God, between others, self, humans and the environment.